RELEVANSI TEORI HUKUM PEMBANGUNAN DAN TEORI HUKUM PROGRESIF DALAM PEMBENTUKAN TEORI HUKUM PANCASILA - Suherman, Heru Andryana (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
This study examines the relevance of the Theory of Development Law and the Theory of Progressive Law within the Indonesian legal system, with particular attention to their role in the developmental process toward the formulation of Pancasila Legal Theory. Pancasila Legal Theory is regarded as a normative foundation that not only reflects the fundamental values of the Indonesian nation but also serves as a philosophical, ideological, and juridical guide in the administration of national law. The research employs a normative legal method with conceptual and historical approaches, conducted through an in-depth examination of relevant legal doctrines. A descriptive analysis is applied to explore the position, function, and role of legal theory in shaping a national legal system grounded in the values of Pancasila as the source of all sources of law. The findings indicate that Pancasila Legal Theory plays a highly significant and strategic role as a foundational framework in the processes of lawmaking, implementation, and enforcement, guiding national law toward substantive justice, social benefit, and the identity and character of the Indonesian nation. Furthermore, this theory ensures that national legal reform remains consistent with the ethical and philosophical principles of Pancasila, thereby enabling the law to function effectively in achieving the goals of the state and the welfare of society.